Viabilidade de projeto de reservatórios de ETA com barras não metálicas - Proni, Gabriel Henrique (Universidade Federal de São Carlos, 2025)
The great works of art such as bridges, viaducts and reservoirs that are in environments with water incidence, have a high maintenance cost of its structural elements, which suffer from the problem of corrosion of the reinforcement. This fragility is recurrent and worries designers. To circumvent this pathology, the market has been seeking innovations with the use of resistant and inert materials for the replacement of conventional steel. In this scenario, the non-metallic bars of glass fiber reinforced polymers (GFRP) have excellent strength-to-weight ratio, making them extremely resistant. In addition, GFRP bars have a high tensile and water resistance, being strongly indicated to structures that suffer from the action of water and chemicals. This material is widely used in works outside of Brazil, as in Europe and Canada, showing good performance against aggressive environments. The present work evaluates the possibility of exchanging steel bars with non-metallic bars for the execution of water treatment plant reservoirs, and its benefits for the durability of the structure, by simulating the design of a reservoir in steel-reinforced concrete and GFRP-reinforced concrete, following the calculation criteria of the Brazilian standards for reinforced concrete, NBR 6118, and for the design of structures reinforced with fiber-reinforced polymer bars, NBR 17196. The simulation results demonstrate higher concrete consumption for GFRP reinforcement due to its cover and similar cost for reinforcement with steel bars and GFRP bars, varying approximately 5%. It is concluded that replacing steel with polymer bars is viable and presents advantages throughout the use and operation of the structure, reduces maintenance and extends its useful life.
Feasibility of design for ETA reservoirs with non-metallic bars
Keywords: Polímeros reforçados com fibra; GFRP; Reservatórios; Corrosão da armadura; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS